Biopsychosocial model as a basis of delivering a care for addicts - Yuliia Asieieva (Kazimierz Wielki University, 2017)
The problem of addictive behavior has a long history in medicine and psychology. Given the current ephemerality of life, a sufficient number of stressful and frustrating circumstances, a large amount of information load contributes to the need to maintain one's mental health. Very often, the mechanisms of psychological protection direct the individual on the path of escape from problems and departure from reality, which leads to the formation of certain types of dependencies. The concept of dependence is considered in the work, some types are outlined and nosological characteristics are described. The principles and basic provisions of building a biopsychosocial model are revealed. The model of providing assistance from the standpoint of biopsychosocial approach and the main functions and tasks of each member of the multidisciplinary team are described. It is noted that the complex of addiction therapy is developed in accordance with the identified factors and type of addiction. In the biological context it is pharmacotherapy, in the psychological context it is psychocorrectional or psychotherapeutic assistance, in the social context it is assistance to a family or an individual member, other social interventions. The essence of our proposed adaptive model is to optimize the use of all resources that are available with their adaptation to the needs of a person with addiction. Note that with the growing number of people with addictions in our country there is an urgent need to create institutions with a "full cycle" of services, where all components of biopsychosocial care could be received by people with different types of addictions, so to speak "through one window".